Projected Implementation of a Website-Based Laundry Services Accounting Information System Using the APIK SI Application - Mustari, Fitrah; Sutisman, Entar; Kartim, Kartim (Advances in Applied Accounting Research, 2024)
Purpose: The study aimed to improve the efficiency of financial recording and transaction management in a laundry service business. For this reason, business owners need an SI APIK accounting application that is easy to use and provides accurate financial information about their business. Research Design and Methodology: The research method employed is qualitative, utilizing data collection techniques that include interviews, observation, and documentation. The types of data used in this research are primary and secondary data. Then, in this study, researchers employed source triangulation as a method to obtain more accurate data. Findings and Discussion: The results showed that the SI APIK application can generate automatic financial reports, including balance sheets, cash flow statements, and profit and loss statements. However, the SI APIK application still has a weakness. If the customer places more than one transaction, the user must input customer data individually each time, as the system deems this transaction inefficient. Implications: This projection is expected to enable SMEs, such as Arafah Laundry, to leverage technology, optimize financial records, enhance business performance, and compete more effectively in the laundry services industry. Future researchers can apply the SI APIK application to other sectors, such as trade, manufacturing, agriculture, animal husbandry, capture fisheries, aquaculture, and individual use.